Chapter 7 Mansions in the Orchard architecture, asylum and community in twentieth-century mental health care - Chaney, Sarah (Social Histories of Medicine, 2019)
This chapter explores the value and relevance of a combined academic and public engagement approach to the history of medicine. The authors consider a specific mental health project at the Bethlem Museum of the Mind, in the context of a longer tradition of service user involvement in mental health research and museology. It is argued that the project's approach presented a unique opportunity for mental health education and the reduction of stigma. These elements of the project informed the historical focus, resulting in a more inclusive history than in many institutional histories of psychiatry, focusing on the importance of space, place and architecture in twentieth-century psychiatry. The chapter concludes that community engagement within a museum setting enriches the history of medicine as a discipline and vice versa.